Comparative study between atropine and hyoscine-N-butylbromide for reversal of detomidine induced bradycardia in horses - Pimenta, E. L. M. [UNESP]; Teixeira Neto, Francisco José [UNESP]; Sa, P. A. [UNESP]; Pignaton, W. [UNESP]; Garofalo, N. A. [UNESP] (Wiley-Blackwell, 2011)
P>Reasons for performing study:Bradycardia may be implicated as a cause of cardiovascular instability during anaesthesia.Hypothesis:Hyoscine would induce positive chronotropism of shorter duration than atropine, without adversely impairing intestinal motility in detomidine sedated horses.Methods:Ten minutes after detomidine (0.02 mg/kg bwt, i.v.), physiological saline (control), atropine (0.02 mg/kg bwt) or hyoscine (0.2 mg/kg bwt) were randomly administered i.v. to 6 horses, allowing one week intervals between treatments. Investigators blinded to the treatments monitored cardiopulmonary data and intestinal auscultation for 90 min and 24 h after detomidine, respectively. Gastrointestinal transit was assessed for 96 h via chromium detection in dry faeces.Results:Detomidine significantly decreased heart rate (HR) and cardiac index (CI) from baseline for 30 and 60 min, respectively (control). Mean +/- s.d. HR increased significantly 5 min after atropine (79 +/- 5 beats/min) and hyoscine (75 +/- 8 beats/min). After this time, HR was significantly higher after atropine in comparison to other treatments, while hyoscine resulted in intermediate values (lower than atropine but higher than controls). Hyoscine and atropine resulted in significantly higher CI than controls for 5 and 20 min, respectively; but this effect coincided with significant hypertension (mean arterial pressures > 180 mmHg). Auscultation scores decreased from baseline in all treatments. Time to return to auscultation scores >= 12 (medians) did not differ between hyoscine (4 h) and controls (4 h) but atropine resulted in significantly longer time (10 h). Atropine induced colic in one horse. Gastrointestinal transit times did not differ between treatments.Conclusion:Hyoscine is a shorter acting positive chronotropic agent than atropine, but does not potentiate the impairment in intestinal motility induced by detomidine. Because of severe hypertension, routine use of anticholinergics combined with detomidine is not recommended.Potencial relevance:Hyoscine may represent an alternative to atropine for treating bradycardia.
Keywords: horse; detomidine; atropine; hyoscine; anaesthesia; gastrointestinal motility